Activation of tetrahydrofuran with 2-((Fluoroalkyl)thio)Benzothiazolium reagents. (19th November 2021) - Maas, Lilian M.; Schmid, Jonas R.; Fasting, Carlo; Voßnacker, Patrick; Mavroskoufis, Andreas; Hopkinson, Matthew N.
Abstract: The ability of BT-SCF3 and related 2-(fluoroalkylthio)benzothiazolium salts to activate tetrahydrofuran (THF) has been investigated. In the presence of carboxylate nucleophiles, ring-opening polymerization reactions affording various fluorinated and non-fluorinated polyethers are observed. Moreover, in the absence of a carboxylate, activation by the benzothiazolium allows for α-deprotonation of THF in the absence of a strong external base. In addition to these experimental studies, the Lewis acidity of BT-reagents is investigated by spectroscopic and quantum chemical methods. Graphical abstract: Image 1